Palaearctic Osmia bees of the subgenera Allosmia and Neosmia (Megachilidae, Osmiini): biology, taxonomy and key to species - Müller, Andreas (Zootaxa, 2022)
Osmia (Allosmia) and O. (Neosmia) are two closely related Palaearctic osmiine bee subgenera (Megachilidae, Megachilinae, Osmiini) comprising eleven and ten species, respectively. Analysis of female pollen loads revealed that the representatives of O. (Allosmia) and O. (Neosmia) are pollen generalists collecting pollen on up to 13 and 17 plant families, respectively. The species of both subgenera exclusively nest in empty snail shells and use chewed leaves as main nest building material, often in combination with fragments of mollusc shells and densely packed small particles, such as small stones, earth crumbs or plant fibers, which are used to barricade the nests. The taxonomic revision of the two subgenera revealed the existence of two undescribed species, O. (Allosmia) gemina spec. nov. from the southern Levant and O. (Neosmia) nigrocalcaribus spec. nov. from the Maghreb. Osmia fossoria Pérez, 1890 syn. nov. and O. decorata Morawitz, 1886 syn. nov. are newly synonymized with O. (Allosmia) lhotelleriei Pérez, 1887 and O. (Allosmia) melanura Morawitz, 1871, respectively, whereas the former synonymization of O. (Neosmia) rosea Friese, 1920 with O. scutispina Gribodo, 1894 is rejected. Osmia (Neosmia) purpurata Ducke, 1899 is regarded as a nomen dubium. Osmia (Allosmia) soror Pérez, 1896 and O. (Neosmia) secunda Peters, 1977 are treated as species rather than as subspecies of O. rufohirta Latreille, 1811 and O. tingitana Benoist, 1969, respectively, due to clear morphological gaps and partly sympatric occurrence. Identification keys for all species of the two subgenera are given.